Indian Journal of Plant Genetic Resources, vol.25, No.1 (2012): Special issue - Indian Society of Plant Genetic Resources (2012)
The special issue has been published in occasion of 25 years of the Indian Journal of Plant Genetic Resources (IJPGR), the official journal of the Indian Society of Plant Genetic Resources (ISPGR). The permission to publish this issue on our web site has been kindly granted by the Indian Society of Plant Genetic Resources (ISPGR) who also hold the copyright. No text, table, diagramme should be reproduced without written permission of the ISPGR.